Digestibilidade aparente e consumo determinados in vivo pelos indicadores externos LIPE®, NANOLIPE® e dióxido de titânio em bovinos alimentados com fubá, farelo de soja e silagem de milho - Henrique Fonseca Lopes (2016)
In this study we used 16 crossbred cattle divided into four groups. The animals were kept in feedlot and fed complete diet consisting of corn silage, corn meal, soybean meal and different sources of minerals. Two experimental trials were conducted. During the first mineral kernel was provided mixed diet, in the second it was forced. The aim of this study was to evaluate the accuracy of external markers LIPE®, NANOLIPE® and titanium dioxide to estimate dry matter intake and digestibility in cattle. The design was completely randomized split plot. The estimated results by the three indicators for intake, digestibility and fecal output did not differ statistically from the total collection data, demonstrating there was no interaction between source of minerals and the results estimated by the indicators. Although when the LIPE® has been used associated with Klason Lignin these indicators were not able to accurately estimate intake.